Pelatihan Desain Grafis dalam Meningkatkan Kemampuan Soft Skill Remaja RT 2 RW 13 Kelurahan Rangkapan Jaya Lama Kota Depok - Roni Fadli; Anggada Bayu Seta; Sri Mulyani (Gapenas Publisher, 2022)
The development of technology is something that cannot be avoided in this life. Human resources must be prepared as well as possible in facing the challenges of the times. Design is the design of a product or object to be made, while graphics is the science of designing dots and lines so that they will form an image that can provide information and relate to the printing process. This graphic design training can be taught starting from the school level so that their soft skills regarding logos, banners, flyers, pamphlets, or other forms are honed. With these soft skills, teenagers can also use them as a source of income by offering photo editing services. In addition, this skill can make it easier for students to edit photos in the midst of increasingly developing technology. The hope is that he can pioneer entrepreneurship by opening graphic design services as a support for the next step in building a creative economy. So that teenagers can start from an early age in sharpening their abilities and mind sets to build potential businesses in the future